Diversity and colonization of butterfly (Lepidoptera) on Pasoso Island, Central Sulawesi - Fauziah ramadhana; Masy'ud, Burhanuddin; Rahman, Dede Aulia (Media Konservasi, 2023)
Various biotic and abiotic environmental factors influence the preservation of butterfly species in an area. The pressure and threat of extinction for butterflies that occupy relatively narrow and isolated habitats such as small islands are pretty large. This study aims to estimate the diversity of butterfly species, predict colonization, predict local extinction of butterflies, and conservation implications to minimize local extinction of butterflies in the habitat type on Pasoso Island, Central Sulawesi Province. Data was collected using field observations in four land cover types (primary forest, gardens, “ecoton” between garden-primary forests, and shrubs) on a 100 m line transect line. Each line transect is divided into point counts, with a distance between points of 100 m. The results of the identification of butterfly species in four habitat types on Pasoso Island found 16 species from 78 individual butterflies belonging to four families (Nymphalidae, Papilionidae, Pieridae, and Lycaenidae). Butterflies in all habitat types on Pasoso Island are in the moderate category. Species diversity in garden habitat types based on the analysis of the Shannon-Wiener index showed higher than other habitat types (H'=1.89), while the Ecoton habitat type has the lowest diversity value (H'=1.06). The results of the t-test showed that there was no significant difference in the diversity of butterfly species in the four habitats. The results showed that colonization and local extinction occurred in butterfly species on Pasoso Island. Four of the nine species are included in the extinct category, namely Apias albina, Family Lycaenidae, Ideopsis juventa, Phalanta alcippe celebensis Wallacea. Five other species were colonized, namely Arhopala araxes, Catochrysops strabo, Catopsilia pomona, Hypolimnas anomala, and Idea blanchardii.